Beyond Sovereign Territory : The Space of Ecopolitics - Kuehls, Thom (Book collections on Project MUSE., 1996)
How should we think about politics in a world where ecological problemsfrom the deforestation of the Amazon to acid raintranscend national boundaries? This is the timely and important question addressed by Thom Kuehls in Beyond Sovereign Territory. Contending that the sovereign territorial state is not adequate to contain or describe the boundaries of ecopolitics, the author reorients our thinking about government, nature, and politics.